TEOLOGI PENGHARAPAN DALAM SURAT PAULUS DAN RELEVANSINYA BAGI MASYARAKAT YANG MENDERITA - Yayuk Sri Paranga; Yofin Apriani Nolasko, Yuniarti Rompa’, Gitari Ayu, Joice Alfista Karru (ADISAM PUBLISHER, 2025)
This article examines the theology of hope in Paul's letters and its relevance for a society experiencing suffering. Paul's hope is understood as the foundation of eschatological faith, affirming the congregation that present suffering is not comparable to the glory to come (Romans 8:18). From Paul's perspective, suffering is a participation in Christ's work, which in turn gives rise to perseverance, patience, and steadfast faith. This theology of hope is not only personal but also communal, as Paul emphasizes that true hope must foster social solidarity and love in the life of the congregation (Galatians 6:9). Thus, Paul's eschatology is not escapist, but rather has a transformative function, providing new meaning, strength, and direction in life amidst the reality of suffering. For modern societies struggling with suffering due to injustice, poverty, and disaster, Paul's eschatology is relevant as a source of comfort, resilience, and motivation to strive for a more dignified life. This research uses a qualitative approach with a literature review through a hermeneutical analysis of Paul's letters and contemporary theological literature. The study's findings indicate that Paul's hope contributes significantly to building a resilient faith and social solidarity in a suffering society